Buletin Peternakan : PERFORMANCES COMPARISON BETWEEN URBAN AND RURAL PIG FARMING SYSTEMS IN MANOKWARI, WEST PAPUA PROVINCE INDONESIA - Desni Triana Ruli Saragih, Lyai, Deny Anjelus (Peternakan UGM, 2015)
Pigs are kept both in urban and rural areas. This research identified the performance differencesÂ between urban and rural farming systems. The study was conducted in Manokwari regency and involvedÂ six districts, i.e. Nothern Manokwari district, Eastern Manokari District, Western Manokwari district,Warmare district, Prafi district and Masni district. Data were analyzed using SPSS version 18.0, anÂ independent-samples T test was run to compare urban and rural pig farming systems. The research foundÂ that there were differences of ages and feeding hours (P<0.05) between those two farming systems.